The Natural Desire of Freedom and Political Inaction: A critique of the meaning of voluntary servitude and natural freedom in the Discourse of Étienne de la Boétie - Fernández Muñoz, Jesús (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
The objective of this paper is the critical analysis of the concept of “voluntary servitude”; and its implications for the freedom posed by Étienne de la Boétie and its relation to the natural desire for freedom. In particular, some ideas from the Discourses of servitude volontaire (1576) are analyzed, starting with a general introduction and the implications of the work in the history of political ideas. The central part of this paper focuses on the problem that society desire to serve, in other words: the desire for slavery and rejection of freedom. For La Boétie, these ideas go against human nature. These problems are those that are discussed from a political theory that goes against the “monolithic thinking”; and that highlights some of the author’s conceptual errors from the perspective of “political”; and the irrelevance of standards of perfection for a feasible political-social organization.